Smart Traffic Light Controller With Flexible Light Period - Tang, Jia Xian; Eh Kan, Chessda Uttraphan (Evolution in Electrical and Electronic Engineering, 2023)
This article presents the development of a smart traffic light controller with a flexible light period to effectively address traffic congestion. In Malaysia, traffic congestion has become a significant problem, and conventional traffic lights with fixed light sequences and timing contribute to the issue. To mitigate this problem, a smart traffic light controller is proposed, which adjusts the light sequences at two adjacent intersections based on the current traffic congestion levels. The methodology involves designing the controller circuit using Verilog HDL, performing functional verification using ModelSim, conducting logic synthesis, and generating the layout using Synopsys for physical implementation. The functional simulation validates the correctness of the controller's outputs according to the specifications. The synthesis results demonstrate a total area of 496 µm2, total power consumption of 146 mW, and compliance with timing specifications. The results indicate that the developed traffic light controller can effectively manage traffic at intersections by dynamically adapting to the prevailing traffic congestion. The flexibility of the proposed technique allows its application to various traffic light configurations. Overall, this study contributes to the field of traffic management by offering an intelligent solution to reduce traffic congestion and improve the efficiency of traffic flow.